2004
DOI: 10.1111/j.1365-2494.2004.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity effects on herbage production and compositional changes in New Zealand hill country pastures

Abstract: A small-plot field experiment on grazed hill country pastures in the North Island of New Zealand was conducted to examine the productivity and compositional characteristics of swards in response to variation in pasture species diversity. The balanced incomplete factorial design incorporated variation in location, slope, soil fertility and combinations of eight plant functional groups (C 4 grasses, annual grasses, annual legumes, perennial C 3 grasses, perennial legumes, perennial forbs, ryegrass and browntop).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
(73 reference statements)
2
23
0
1
Order By: Relevance
“…Research conducted at several scales in a variety of managed grasslands has indicated that species-rich forage mixtures can reduce weed invasion [17][18][19]21,[38][39][40] . Combining forage species into functional mixtures has been successful in reducing the establishment of invasive plants in rangelands 41 .…”
Section: Invasion Resistancementioning
confidence: 99%
“…Research conducted at several scales in a variety of managed grasslands has indicated that species-rich forage mixtures can reduce weed invasion [17][18][19]21,[38][39][40] . Combining forage species into functional mixtures has been successful in reducing the establishment of invasive plants in rangelands 41 .…”
Section: Invasion Resistancementioning
confidence: 99%
“…However, based on the total number of species present (i.e. including weeds), no consistent effects were found (Bezemer and van der Putten 2007;Dodd et al 2004). It has been a principle of ecological theory that the assembly of species in a given habitat depends on the niches present.…”
Section: Diversity and Productivitymentioning
confidence: 99%
“…Concerning the role of phytodiversity in grasslands, positive effects on ecosystem services have repeatedly been pointed out. Thus, increased diversity has been suggested to lead to an enhanced production (Bai et al 2007;Bullock et al 2007;Dodd et al 2004;Hector et al 1999;van Ruijven and Berendse 2003;Weigelt et al 2009;Yachi and Loreau 1999) as well as to an improved stability, sustainability and efficiency of grassland production systems (Caldeira et al 2001;Hooper et al 2005;Hooper and Vitousek 1998;Kahmen et al 2006;Luck et al 2003;Niklaus et al 2006;Oelmann et al 2007;Roscher et al 2004Roscher et al , 2008Scherer-Lorenzen et al 2003;Tilman et al 2006;Yachi and Loreau 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although considerable information exists about the relationship between the application of phosphorus fertiliser, pasture growth and the influence of topography (Lambert et al 1983(Lambert et al ,2000Gillingham et al 1998;Lopez et al 2003;Dodd et al 2004), up until now we have lacked the mechanism to apply variable rates of fertiliser to match the potential of the land. A variable rate control system designed by the New Zealand Centre for Precision Agriculture, Massey University in conjunction with Wanganui Aerowork Ltd has been developed, and commercial trials using this system have resulted in a ground resolution of 18 × 18 m. Figures such as 15-20 kg superphosphate SU -1 yr-1 wintered have been used as a broad recommendation (Morton & Roberts 1999); however the within-field variability of hillcountry pasture production is often overlooked.…”
Section: Introductionmentioning
confidence: 99%